Parametric study on the settlement improvement factor of stone column groups / Ng Kok Shien and Tan Siew Ann - Ng, Kok Shien; Tan, Siew Ann (Universiti Teknologi MARA Pulau Pinang, 2014)
In the design of floating stone column groups, the footprint replacement ratio is of great importance when attempting to reduce the amount of settlement. This paper shows the parametric study performed to determine the effects of other contributing parameters such as friction angle of column material, thickness of granular bed, column stiffness, soil stiffness and their relationships with footprint replacement ratio and loading intensity. The study was conducted using finite element method via the commercial geotechnical software PLAXIS. The parametric results have shown that the friction angle of the stone column material and the thickness of granular bed have the most profound effect on the settlement improvement factors. The influence of these factors are larger if the numbers of columns in a group is smaller, and the vice versa. Column stiffness is of less influence compared to soil stiffness and when the modulus ratio is larger than 20, the influence of these two parameters are very small and negligible. The stress transfer mechanism and the yielding characteristic were discussed pertaining to the influence of the key parameters on the settlement improvement factor. Finally, design recommendation was given to help the practicing engineer in designing the stone column group.